Packing Constant in Orlicz Sequence Spaces Equipped with the p-Amemiya Norm - Xin He; Jijie Yu; Yunan Cui; Xin Huo (Abstract and Applied Analysis)
The problem of packing spheres in Orlicz sequence space lΦ,p equipped with the p-Amemiya norm is studied, and a geometric characteristic about the reflexivity of lΦ,p is obtained, which contains the relevant work about lp  (p>1) and classical Orlicz spaces lΦ discussed by Rankin, Burlak, and Cleaver. Moreover the packing constant as well as Kottman constant in this kind of spaces is calculated.